Imagination and Symbolization in Sanskrit Poetical Literature - Balakailasanathasarma, M. (University of Kelaniya, 2018)
The examination of the processes of imagination and 'symbolization' and the study of their relationship to human experience has contributed greatly to the understanding of the human mind. Especially Sanskrit poetical literature laid claim to an ample heritage of mythology and symbolism. Yet, a strict appraisal of the nature and functions of images and symbols in their literary connotation has not received adequate attention. This study focused on this gap using critical analytical method by analyzing the nature and functions of images and symbol in Sanskrit Poetics. Objective of this study is to identify Imagination and Symbolization in Sanskrit Poetical Literature. Imagination and symbolization in Sanskrit poetical literature is not merely a borrowing of the devices formulated by grammarians and linguists or the copying out in its entirety of a well-established symbolism of a religious culture. The poets were indeed compelled to draw from ancient religion, folklore and mythology the symbols they required, but in doing so they did not always follow traditional lines for the medium of poetry made it necessary to adapt them or sometimes transform them. To conclude this paper in Sanskrit poetics the ideas underlying the concepts of 'image' and 'symbol' appear to have been generally recognized but the undue emphasis laid on the aspects of imagery dealing with 'figurative expression' (alankara), in the early period, prevented a clear formulation of the principles. An increasing awareness of the critical approach to literature that came in the wake of analytical studies of language, grammar and logic brought about critical attitudes in the conception of imagery and symbolism of poetry, in Sanskrit. From then on critics were not only interested in examining the functions of these literary devices but also attempted to relate them to aesthetic theories of Sanskrit poetry.
Keywords: Imagination; Mythology; Religion; Sanskrit; Symbolization